2019
DOI: 10.3390/educsci9020105
|View full text |Cite
|
Sign up to set email alerts
|

eSports in K-12 and Post-Secondary Schools

Abstract: eSports is a rising modality of sports entertainment in the United States and has growing implications for education. Providing competitive eSports teams in schools satisfies the growing desire to train and educate students on the skills emphasized in STEM and Career Technical Education (CTE) education, as well as in programs such as English and Language Arts. eSports develop the soft skills universities and employers like to see in a student graduating from high school. As the market continues to grow for eSp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…In its implementation, gamification or game-based learning adapts game elements to engage learners to take part in learning to build learners' problemsolving skills (Kapp, 2012). In countries with high educational rank, such as Ukraine, Poland, US, China, and Netherland, gamification has been familiarized and used by teachers, including English teachers that showed substantial results (Glowacki, Kriukova, & Avshenyuk, 2018;Rothwell & Shaffer, 2019;Antonaci, Klemke, & Specht, 2019). In Indonesian contexts, gamification is started to get familiarized, as well, despite its limited researches.…”
Section: -47mentioning
confidence: 99%
“…In its implementation, gamification or game-based learning adapts game elements to engage learners to take part in learning to build learners' problemsolving skills (Kapp, 2012). In countries with high educational rank, such as Ukraine, Poland, US, China, and Netherland, gamification has been familiarized and used by teachers, including English teachers that showed substantial results (Glowacki, Kriukova, & Avshenyuk, 2018;Rothwell & Shaffer, 2019;Antonaci, Klemke, & Specht, 2019). In Indonesian contexts, gamification is started to get familiarized, as well, despite its limited researches.…”
Section: -47mentioning
confidence: 99%
“…Supporting traditional sports is a well-known practice, but there is a rising trend of providing sponsorships to eSport teams [ 16 , 17 ]. The popularity of tournaments that are considered to be eSports is drastically raising in the abovementioned age groups [ 18 ]. In 2017, Twitch, a live streaming platform for gamers, had a higher viewership when compared to CNN and MSNBC, and had a viewership that was to similar to ESPN at any given time [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is currently a dearth of research on eSports since there was some opposition to gaming on campuses previously. However, "much of the resistance in bringing eSports teams to education is due to the lack of awareness and understanding of how a video game competition can foster the skills desired in tomorrow¢s society" (Rothwell & Shaffer, 2019, section 8). Reitman et al (2020) reviewed available published literature and noted that "eSports research has developed from nonexistent to a field of study spread across seven academic disciplines" (p. 1) including business, sports science, cognitive science, informatics, law, media studies, and sociology and is not confined to only a few localities but reported that the internationality of eSports is now a reality.…”
Section: Theoretical Underpinningsmentioning
confidence: 99%